Traumatic Testimony and Remembering in “The Lankuri Tree will Blossom Again” - Pokharel, Badri Prasad (Molung Educational Frontier, 2019)
This paper examines Rajendra Bimal’s “The Lankuri Tree Will Blossom Again” is a post-conflict narrative which describes a poor and insurgency affected family living in the very hinterland of Nepal and their traumatic experience: fleeing away from home for safety, leaving the very adorable daughter to an unknown person and determining to live with the situation going on during the Maoist war. The story has been analyzed from the author’s narrative of adversity and trauma along with some thematic description. The themes include: perception of impending violence, trauma in the lives of commoners and gradual development from severe stress to determination to face the challenge. Nepal’s ten years long insurgency, a great loss in the country in the name of bringing peace and solidarity, has taken the lives of thousands of people and millions of others have been mentally and physically wounded. Hence, they are in trauma and their testimony has been a significant inscription of the history for those who want to know how innocent and common people were targeted. Here, I examine the story from personal trauma to the conflict generated consequences in the lives of affected people using content analysis of the personal, group, and socio-political factors associated with Bimal’s understanding of the People’s War, and of violence. Discussing the expected findings, this article centers on the common people’s fear of war and embedded peace in the country. Rajendra Bimal’s “The Lankuri Tree Will Blossom Again”, as a traumatic testimony of the insurgency, has been analyzed in this article to bring out the facts.